Numerical simulation of the buoyancy flow between two concentric cylinders with azimuthal variable heating - Medina Jiménez, Lucía; Serrano-Aguilera, Juan José; Blanco-Rodríguez, Francisco José; Parras-Anguita, Luis (Prof JP Meyer. Proceedings of the 15th International Conference on Heat Transfer, Fluid Mechanics and Thermodynamics (HEFAT2021), 2021)
In this work, we present novel results of the buoyancy driven flow between two concentric cylinders, when an azimuthal thermal gradient is imposed to the inner cylinder. To accomplish that, angular-dependent temperature distribution (sinusoidal function) is imposed at that surface so that a fourth parameter is added to the problem (L). This new parameter accounts for the ratio of amplitude of temperature (amplitude of sinusoidal function) in the inner cylinder to the difference of temperature between the inner and outer cylinder. When this new parameter is zero, one retains the same solutions shown in J.J. Serrano-Aguilera et al. [1] (isothermal conditions in both cylinders) but increasing this parameter, the imposed angular gradient in the inner cylinder induces flow structure changes and the subsequent modification in the average equivalent conductivity.
Keywords: Mecánica de fluidos; Buoyancy driven flow; Variable azimuthal heating